Glaucoma and cognitive function trajectories in a population‐based study: Findings from the health and retirement study. Issue 10 (22nd June 2022) - Kolli, Ajay; Kabeto, Mohammed; McCammon, Ryan; Langa, Kenneth M.; Ehrlich, Joshua R.
Abstract: Introduction: Prior studies on the association of glaucoma and cognitive function have reported mixed results. Methods: The Health and Retirement Study (HRS) is a nationally representative panel survey of Americans age ≥ 51 years. HRS‐linked Medicare claims data were used to identify incident glaucoma cases (by glaucoma type). Cognitive function was measured using the Telephone Interview for Cognitive Status (TICS), administered in each wave (every 2 years). Separate linear mixed models were fitted with either prevalent or incident glaucoma as a predictor of TICS trajectories and adjusting for age, race/ethnicity, educational attainment, gender, and medical history. Negative model estimates indicate associations of glaucoma with worse cognitive function scores or steeper per‐year declines in cognitive function scores. Results: Analyses of prevalent glaucoma cases included 1344 cases and 5729 controls. Analyses of incident glaucoma included 886 cases and 4385 controls. In fully‐adjusted models, those with prevalent glaucoma had similar TICS scores to controls ( β = 0.01; 95% Confidence Interval [CI]: −0.15, 0.18; p = 0.86). However, in those with incident glaucoma, we detected a statistically significant association between glaucoma and lower TICS scores ( β = −0.29; 95% CI: −0.50, −0.08; p = 0.007). However, there was no statistically significant association between either prevalent or incident glaucoma and per‐year rates of change in TICS scores. When categorizing glaucoma by type (primary open angle glaucoma, normal tension glaucoma, or other glaucoma), no significant associations were detected between either prevalent or incident glaucoma and levels of or rates of change in TICS scores in fully covariate adjusted models. Conclusion: The observed associations between glaucoma and cognitive function were small and unlikely to be clinically meaningful. Compared to prior studies on this topic, this investigation provides robust evidence based on its larger sample size, longitudinal follow‐up, and repeated measures of cognitive function in a population‐based sample.